Politik Hukum Perubahan Sifat Lembaga Badan Pengawas Pemilihan Umum: (Studi: Perubahan Sifat Badan Pengawas Pemilihan Umum Kabupaten Kota Menjadi Definitif Dan Pelaksanaan Kewenangan Badan Pengawas Pemilihan Umum Kota Sawahlunto Pada Pemilihan Umum Tahun 2019) - Zul Hendri Nov (Jurnal Selat, 2020)
Legal politics is intended as a guideline for determining basic policies regarding the form, direction and purpose of legal formation. In terms of achieving legal objectives institutions need to realize it. To safeguard the sovereignty of the people so that they are channeled through the elections properly, an election supervisory body is needed. After the birth of the new Election Law, the interesting thing that happened was the gradual process of increasing the institutional status of election supervisors starting from the central level to the district / city level. In this paper, the authors look at the process of changing the institutional nature of Bawaslu at the district / city level which becomes a permanent institution through the new election law. The method used is qualitative with an empirical Normative legal approach. At the end of this paper, the writer concludes that it is important to increase the authority of Bawaslu at the municipal level by making it permanent. Through the exercise of authority given to Bawaslu, Bawaslu of Sawahlunto city can maintain the sovereignty of the people and realize fair elections. As a suggestion in the exercise of authority, the author sees the need to establish a special electoral justice system. Where in terms of election criminal enforcement, Bawaslu is no longer bound by the subjective views of the Prosecutors and the Police in Gakkumdu, so that they are independent in carrying out the prosecution and enforcement of Election Law. Keywords: Keywords: Bawaslu, Authority, Institutional Nature